CONSTITUTIONAL ENGINEERING IN THE PRESIDENTIAL AND VICE PRESIDENTIAL ELECTIONS (ANALYSIS OF THE CONSTITUTIONAL COURT'S DECISION NO. 62/PUU-XXII/2024 CONCERNING THE ELIMINATION OF THE PRESIDENTIAL THRESHOLD) - Muhammad Agung Rizki Satria; Muhammad Nasir Sitompul (Inspiring Law Journal, 2026)
This study aims to analyze constitutional engineering in the presidential and vice presidential election systems in Indonesia through a study of the Constitutional Court Decision No. 62/PUU-XXII/2024 which abolished the presidential threshold provisions. Over the past two decades, the threshold for presidential candidacy of 20% of the House of Representatives seats or 25% of the national valid vote has sparked debate because it is considered to limit the constitutional rights of political parties and narrow the people's choice in elections. Through the decision, the Court emphasized that Article 222 of Law Number 7 of 2017 is contrary to Article 6A paragraph (2) of the 1945 Constitution, because the constitution does not stipulate a certain percentage of support requirements for presidential candidacy. This research uses normative legal methods with legislative, case, and conceptual approaches, and is supported by an analysis of constitutional engineering doctrines (Giovanni Sartori), democratic theory (Robert Dahl), and the principle of proportionality. Data were collected through literature studies on primary legal materials (1945 Constitution, Law No. 7/2017, Constitutional Court Decision) and secondary (academic literature, journals, and expert opinions). The results of the study show that before the Constitutional Court Decision No. 62/PUU-XXII/2024, the presidential threshold system formed an elitist political configuration and closed the space for inclusive competition. Through teleological and proportional interpretation, the Court returns the presidential nomination mechanism to the essence of people's sovereignty by opening access for all political parties participating in the election. This decision is a tangible form of judicial constitutional engineering, where the Constitutional Court not only upholds norms, but also redesigns the democratic structure to be more representative, equitable, and in line with the principles of Indonesia's constitutional democracy.